The Role of Financial Management as a Mediator in the Relationship between Literacy and Investment in the Research Community - Royani, Ida; Gusni (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
This study looks at how financial literacy, education, and income affect investing decisions among professionals in Indonesia, with financial management acting as a middleman. This study used a quantitative method with a full sample of 155 employees at the Smart City & Community Innovation Center (SCCIC). It collected data through structured questionnaires and analyzed it using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that being financially literate and educated makes people better at managing their money, which in turn has a big effect on their investing choices. Income has a direct effect on investment selections, but it doesn't have a big effect on how people manage their money. Interestingly, being financially educated has a direct negative effect on investment decisions, which means that those who know more about money tend to be more careful and picky investors. The way people manage their money is an important link between literacy, education, and investing choices. These results show how important it is to teach people about money in a way that focuses on behavior to encourage smart and long-term investment participation. The study gives policymakers and financial educators useful advice on how to help people in developing countries get better investment results. Keywords: Financial literacy;Education;Income;Financial management;Investment decision